Targeted Nanotheranostics for Future Personalized Medicine: Recent Progress in Cancer Therapy - Jo, Sung Duk; Ku, Sook Hee; Won, You-Yeon; Kim, Sun Hwa; Kwon, Ick Chan (IVYSPRING INT PUBL, 2016)
Recently, many theranostic nanomaterials have been developed by integrating therapeutic and diagnostic agents in a single regimen. Real-time visualization of nano drug carrier biodistributions, drug release processes and therapeutic responses can provide critical information needed for dynamically optimizing treatment operations in a personalized manner in real time. This review highlights recent progresses in the development of multifunctional nanoparticles possessing both therapeutic and imaging functionalities for cancer therapy. The advantages of using nanoparticle platforms are discussed. Examples demonstrating various combinations of imaging and therapeutic modalities are highlighted.
Keywords: GLYCOL CHITOSAN NANOPARTICLES; INTENSITY FOCUSED ULTRASOUND; POSITRON-EMISSION-TOMOGRAPHY; UP-CONVERSION NANOPARTICLES; IN-VIVO; CONTRAST AGENTS; DRUG-DELIVERY; MULTIFUNCTIONAL NANOPARTICLES; GOLD-NANOPARTICLES; UPCONVERTING NANOPARTICLES